Impact of PEDOT:PSS Concentration and Heat Treated on Compositional and Some Optical Properties for Graphene Oxide Thin Films - Qasim, Saja; AbdulAmeer, Ameer F. (Iraqi Journal of Science, 2022)
In this study the as-deposited and heat treated at 423K of conductive blende graphene oxide (GO) / poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) thin films was prepared with different PEDOT:PSS concentration (0, 0.25, 0.5, 0.75 and 1.0)wt% on pre-cleaned glass substrate by spin coating technique. The energy dispersive X-ray Analysis (EDX) show the existence of higher amount of carbon and oxygen related to hydroxyl and carbonyl groups. X-ray diffraction (XRD) analysis of the as-deposited and annealed GO/PEDOT:PSS thin films blend indicated that the film prepared show broad peak around 8.24 corresponding to the (001) level refers to GO, this peak shifted to the lower 2θ with increasing PEDOT:PSS concentration. These results of Fourier transform infrared spectroscopy (FTIR) support the EDX measurement and confirm all the bonds of mixed compounds before and after annealing process. UV-visible spectra of the GO was registered for investigation the peak at 224 nm along with the shoulder at 260 nm. After blending ,there are a small shifts in the peaks locations toward the red shift wavelength with increase the concentrations of PEDOT:PSS, while after heat the peaks locations shift toward the blue shift wavelength.